“I am very critical of my body, but I am not a worthless person”: A qualitative investigation of internalized weight stigma in Denmark - Davidsen, Emma; Pico, Majken Lillholm; Sandøe, Peter; Lund, Thomas Bøker (Frontiers in Psychology, 2023)
Aim: The aim of this study was to explore how two of the main dimensions of internalized weight stigma (IWS), namely weight-related self-devaluation and distress, play out in the lives of people with excess weight (EW), and to study whether there are further dimensions of IWS. Method: Ten informants with EW were included in this study. The sample size was determined prior to data collection based on available resources at the time of data collection. All informants both participated in in-depth interviews and responded to the questionnaire WBIS-2F consisting of the two subscales: weight-related self-devaluation and distress. Their interview accounts were thematically coded and compared with their scoring on WBIS-2F. Findings: Seven themes were identified from the in-depth interviews: 1) devaluation of competencies, 2) self-blame, 3) bodily devaluation, 4) ambivalence, 5) anticipated stigma 6) coping strategies and, 7) mental well-being. Overall, the informants scored low on the WBIS-2F subscale weight-related self-devaluation and high on the subscale weight-related distress. The qualitative findings echo the informants’ scoring on WBIS-2F. However, novel aspects of IWS not covered by WBIS-2F were also identified. In particular, bodily devaluation presented itself as an integral part of IWS. Conclusion: The two current dimensions of WBIS-2F were retrieved, but important additional aspects of IWS were also identified. Future research is needed to evaluate and test both qualitatively and quantitatively whether the additional aspects of IWS identified in this exploratory examination are separate constructs of IWS.